A New Smart Cargo Cabinet Application for Unmanned Delivery in Smart Cities - Yetis, Hasan; Karakose, Mehmet (Ieee, 2018)
Today, e-commerce, which basically needs the internet and shipping, is becoming more common. Nevertheless, the absence of buyers from home is a barrier to the delivery of shipments. In this paper, it is proposed a new way that makes possible the totally unmanned delivery with the help of smart buildings as a part of smart city. Furthermore, smart cargo cabinet concept model, which removes the necessity of having buyers at home, is proposed to be used in transition process. With sample scenarios, these models are explained. Both these proposed approaches help in reducing the number of undelivered cargoes. Removing the failed deliveries due to customers who are not at home, has positive effects on economy, traffic, and energy, which are the main objectives of the smart city.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: intelligent buildings; smart cargo cabinet; smart city; unmanned delivery